Quantitative assessment of the impact of precipitation and vegetation variation on flooding under discrete and continuous rainstorm conditions. (November 2022) - Sheng, Fei; Liu, Shiyu; Zhang, Ting; Liu, Guihua; Liu, Zhao
Highlights: Put forward the definition method of discrete rainstorm and continuous rainstorm. Parameters of HEC-HMS model under different rainstorm were calibrated. Contribution rate of precipitation and vegetation variation to flood was calculated. Positive and negative role of vegetation were discussed under continuous rainstorm. Abstract: Precipitation and vegetation are two critical factors affecting floods in watersheds. A quantitative evaluation of their contribution to flooding is of great scientific significance for vegetation construction and water resource management. Thus, this study took the Pengchongjian small watershed, located in Southeastern China, as the research object. Based on geographic and hydrometeorological data from 1983 to 2017, the characteristics of rainstorm and flood in the watershed were analyzed. Meanwhile, the Hydrologic Engineering Center's Hydrologic Modeling System (HEC-HMS) model was used to quantitatively calculate precipitation and vegetation variation contribution rates to the total flood volume and peak flow under discrete and continuous rainstorm conditions. The results indicated that the rainstorm volume and total flood volume showed a non-significant upward trend in the two periods of 1983–2003 and 2004–2017, and the variation coefficient of total flood volume was higher than that of rainstorm volume. At the same time, the periodic variation characteristics of rainstorm volume and total flood volume in 1983–2017 were basically consistent. The HEC-HMS model offered good simulation of discrete and continuous rainstorm floods, and the simulation accuracy met our requirements. Under the condition of discrete rainstorm, the average contribution rates of precipitation and vegetation variation to the total flood volume were 58.9 % and 41.1 %, and to the peak flow were 54.2 % and 45.8 %, respectively. In the case of continuous rainstorm, when the contribution rate of vegetation variation was positive, the average contribution rates of precipitation and vegetation variation to the total flood volume were 72.2 % and 27.8 %, and to the peak flow were 84.9 % and 15.1 %, respectively. When the contribution rate of vegetation variation was negative, the average contribution rates of precipitation and vegetation variation to the total flood volume were 125.0 % and −25.0 %, and to the peak flow were 132.1 % and −32.1 %, respectively. These results could provide a basis for the comprehensive management of soil and water loss, water resource planning, vegetation construction, and hydrological benefit evaluation.